2007
DOI: 10.2169/internalmedicine.46.6422
|View full text |Cite
|
Sign up to set email alerts
|

SIADH is only an Atypical Clinical Feature in a Patient with Prolactinoma

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…SIADH rarely occurs in patients with sellar lesions and is usually due to compression and dislocation of the stalk [7][8][9][10][11][12][13][14]. In this study, we document a unique case of SNB presenting with SIADH due to ectopic production of antidiuretic hormone (ADH) in neoplastic cells.…”
Section: Introductionmentioning
confidence: 95%
“…SIADH rarely occurs in patients with sellar lesions and is usually due to compression and dislocation of the stalk [7][8][9][10][11][12][13][14]. In this study, we document a unique case of SNB presenting with SIADH due to ectopic production of antidiuretic hormone (ADH) in neoplastic cells.…”
Section: Introductionmentioning
confidence: 95%
“…Differential diagnosis of hyponatremia SIADH should be considered as one of the possible differential diagnoses of hyponatremia [3][4][5]. Previous reports have shown that local and mechanical stressors that compress the pituitary stalk influence the excessive release of ADH.…”
Section: Pathogenesis Of Secondary Adrenal Insufficiencymentioning
confidence: 99%
“…Secondary adrenal insufficiency, one of the major causes of hypo-osmotic hyponatremia, results from hypothalamic or hypophyseal disorders [1]. Causes of pituitary adenoma-induced hyponatremia include hypopituitarism in association with concurrent dysfunction of the pituitary-adrenal axis [2] and the syndrome of inappropriate secretion of ADH (SIADH) [3][4][5]. Among the differential diagnoses of hyponatremia, several reports suggest that a pituitary gland corticotrophic adenoma may lead to impaired processing of mature ACTH.…”
Section: Introductionmentioning
confidence: 99%
“…Valparaíso, Chile . L a hiponatremia (HNA) como forma de presentación de un hipopituitarismo (HPT) ha sido comunicada en diversas situaciones clínicas, pero infrecuentemente como primera manifestación de un tumor hipofisario (TH) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . El objetivo de esta comunicación fue conocer la frecuencia y características clínicas de esta forma de presentación de los THs.…”
Section: Hyponatremia Associated To Pituitary Adenomas Report Of Thrunclassified
“…Aunque los TH's son una causa común de hipopituitarismo, la HNA sintomática rara vez es su motivo de presentación clínica 6,7 . La HNA se ha observado asociada a adenomas, craneofaringiomas, prolactinomas, quistes, schwanomas, meningiomas, aneurismas, carcinoma nasofaríngeo y metástasis de carcinomas 8,12,[16][17][18][23][24][25][26][27][28] .…”
Section: Casos Clínicosunclassified